The Conceptual Framework of Crimes Againts Humanity in Historical Context and Indonesian Law - Maskun, Maskun (Indonesia Law Review, 2012)
The rapid ratification of the Rome Statute of the International Criminal Court (ICC) and the orderly election of its judges and prosecutor believe the radical nature of the new institution. Indonesia is one of countries that rejected the International Criminal Court (ICC) Statute. Indonesia’s reason at that time was that Indonesian sovereignty would be threatened or its national security would be compromise. Interestingly, some of the crimes within the Rome Statute jurisdiction (Article 5 of the Rome Statute) had been adopted by Indonesia in its domestic law such as the Law No. 26 year 2000 concerning Human Rights Court. Jurisdiction of the Law No. 26 year 2000 is and genocide and crimes against humanity. The Law No. 26 year 2000 also adopts the idea of Ad hoc tribunal that is possible to apply ex post facto justice. Finally, it plays important role in order to protect Indonesian interest and to fulfill international community point of views.